A Randomized Controlled Trial of Misoprostol and Sulprostone to End Pregnancy after Fetal Death. (30th June 2009) - Van Mensel, Kristin; Claerhout, Filip; Debois, Patrick; Keirse, Marc J. N. C.; Hanssens, Myriam
Abstract : Objective . To compare effectiveness, side effects, and patients' perception of vaginal misoprostol versus intravenous sulprostone for ending pregnancy after fetal death between 14 and 42 weeks gestation. Method . Multicenter randomized controlled trial, using block randomization, central allocation, and prior power analysis. Outcome measures . Induction-delivery interval, gastrointestinal side effects, use of analgesia, pain perception, pyrexia, placental retention, hemorrhage, and women's opinions. Results . Of 176 women aimed for, 143 were randomized over 7 years, of whom 4 were excluded. There was no difference in delivery within 24 and 36 hours: 91.4% and 97.1% with misoprostol (n = 70 ) versus 85.5% and 92.8% with sulprostone (n = 69 ). There was no difference in either gastrointestinal side effects, as reported by the women and their caregivers, use of analgesia, women's pain perception, blood loss or placental retention. Hyperthermia≥ 38°C was more common with misoprostol (24.3%) than with sulprostone (11.6%; difference: +12.7%; 95% CI: +1.2% to +25.3%) and related to the total dose used. Acceptability of both induction methods was similar except for freedom of movement, which was substantially in favor of misoprostol (lack of freedom reported with misoprostol in 34.3% versus 63.8% with sulprostone; difference: −29.5%; 95% CI: −13.6% to −45.4%). Conclusions . Misoprostol and sulprostone are similarly effective with little difference in side effects except for hyperthermia, related to the dose of misoprostol used, and women's reported lack of mobility with intravenous sulprostone. Effectiveness of both methods increased with gestational age.